Human metallo-β-lactamase enzymes degrade penicillin - Seydina M. Diene (Nature Portfolio, 2019)
Abstract Nonribosomal peptides are assemblages, including antibiotics, of canonical amino acids and other molecules. β-lactam antibiotics act on bacterial cell walls and can be cleaved by β-lactamases. β-lactamase activity in humans has been neglected, even though eighteen enzymes have already been annotated such in human genome. Their hydrolysis activities on antibiotics have not been previously investigated. Here, we report that human cells were able to digest penicillin and this activity was inhibited by β-lactamase inhibitor, i.e. sulbactam. Penicillin degradation in human cells was microbiologically demonstrated on Pneumococcus. We expressed a MBLAC2 human β-lactamase, known as an exosome biogenesis enzyme. It cleaved penicillin and was inhibited by sulbactam. Finally, β-lactamases are widely distributed, archaic, and have wide spectrum, including digesting anticancer and β-lactams, that can be then used as nutriments. The evidence of the other MBLAC2 role as a bona fide β-lactamase allows for reassessment of β-lactams and β-lactamases role in humans.